France : Selected Issues. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper reviews developments in health care spending in France and discusses the recent measures to improve the functioning of the system and contain costs. It argues that by addressing many of the issues that had bedeviled past reforms, the new measures offer a reasonable hope of containing France's health expenditures. The paper presents a brief review of the institutional background and of past trends in health care spending and also offers an analysis of the major forces behind the recent and projected growth in expenditure.